Concentrated Disadvantage and the Incarceration of Youth: Examining How Context Affects Juvenile Justice. (May 2013) - Rodriguez, Nancy
Objectives: Attribution theory is used to frame a study on concentrated disadvantage and youth correctional confinement. Method: Population of delinquent referrals and a random sample of 50 youth case file records from a large urban juvenile court in the southwest are analyzed. Results: Black and Latino/Latina youth were more likely than their White counterparts to be institutionalized. Youth from areas with high levels of concentrated disadvantage were more likely to be confined than youth from more affluent areas. Court officials' perceptions of disadvantage play an important role when deciding whether youth should remain in the community or be incarcerated. Conclusions: Race, ethnicity, and concentrated disadvantage play a significant role in juvenile justice. Court officials perceive areas of disadvantage as high risk and dangerous for youth. Unfortunately, correctional confinement appears to be one way to address youths' vulnerable state. This study sheds light on the importance of economic landscapes in the administration of justice and the delivery of services.